PENGARUH PEMBERIAN PENGUATAN TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN 018 RANTAU SIALANG KECAMATAN KUANTAN MUDIK KABUPATEN KUANSING - Yulia Citra; Syahrilfuddin Syahrilfuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research is in the background by the weakness of student learning motivation in the teaching and learning process, one of which is characterized by students tend to be passive and less enthusiastic. The purpose of the study was to find out whether there was an effect of giving reinforcement to students 'learning motivation and how much influence the giving of reinforcement on students' learning motivation. The approach in this study is quantitative with the type of experimental research, the design of this study is pre-experimental. The pre-experimental design used in this study was one pretest-posttest group. The subjects in this study were 27 grade V students of SDN 018 Rantau Sialang with 8 men and 19 women. The variables in this study are the variables of giving reinforcement and student motivation. Data collection using documentation and questionnaires. Validity test using Pearson product moment formula and reliability test using Alpha formula. The analysis prerequisite test used the normality test with the Kolmogrov-Smirnov One Sample test using SPSS 17.0 for windows. Hypothesis testing uses the t test with the help of SPSS and the last effect test. The results showed that there was an effect of giving reinforcement to students' learning motivation, as evidenced by the results of the t test at a significant level of 1% and 5% namely tcount> ttable or at level 1% (7,751> 1,298) at the level of 5% (7,751> 1,674). Calculation of the effect test (effect size) obtained by ES is 3.146, this figure is included in the high category because the effect size is more than 0.8. It was concluded that giving reinforcement had an effect on the learning motivation of V grade students of SDN 018 Rantau Sialang Kecamatan Kuantan Mudik Kabupaten Kuansing with a high category